Silencing of ASXL1 impairs the granulomonocytic lineage potential of human CD34+ progenitor cells - Davies, C; Yip, B; Fernandez-Mercado, M; Woll, P; Agirre, X; Prosper, F; Jacobsen, SE; Wainscoat, J; Pellagatti, A; Boultwood, J (2013)
The ASXL1 gene encodes a chromatin-binding protein involved in epigenetic regulation in haematopoietic cells. Loss-of-function ASXL1 mutations occur in patients with a range of myeloid malignancies and are associated with adverse outcome. We have used lentiviral-based shRNA technology to investigate the effects of ASXL1 silencing on cell proliferation, apoptosis, myeloid differentiation and global gene expression in human CD34+ cells differentiated along the myeloid lineage in vitro. ASXL1-deficient cells showed a significant decrease in the generation of CD11b+ and CD15+ cells, implicating impaired granulomonocytic differentiation. Furthermore, colony-forming assays showed a significant increase in the number of multipotent mixed lineage colony-forming unit (CFU-GEMM) colonies and a significant decrease in the numbers of granulocyte-macrophage CFU (CFU-GM) and granulocyte CFU (CFU-G) colonies in ASXL1-deficient cells. Our data suggests that ASXL1 knockdown perturbs human granulomonocytic differentiation. Gene expression profiling identified many deregulated genes in the ASXL1-deficient cells differentiated along the granulomonocytic lineage, and pathway analysis showed that the most significantly deregulated pathway was the LXR/RXR activation pathway. ASXL1 may play a key role in recruiting the polycomb repressor complex 2 (PRC2) to specific loci, and we found over-representation of PRC2 targets among the deregulated genes in ASXL1-deficient cells. These findings shed light on the functional role of ASXL1 in human myeloid differentiation. © 2013 Blackwell Publishing Ltd.